Evaluation of the Soil Elastic Modules by Means of Box Tests - Bencat, Jan; Cibulka, Milan; Hrvol, Milan (Communications - Scientific letters of the University of Zilina, 2008)
The experimental measurements results of static and dynamic elastic modules (Es, ED) and initial tangent modules (Go, Eo) of soils evaluated by means of box tests application techniques for calculation of these modules via static and dynamic loading half – space test means (SLT, DLT) and via shear wave velocity measurements tests are given. In the cross – hole method, body wave velocities are commonly evaluated from visual determinations of arriva timel of the waves at receivers. Additional time – determination techniques based on correlation and spectral analysis are discussed. The correlation technique is based on the cross – correlation function of waveforms recorded by two receivers. The spectral analysis technique is based on the phase of cross – energy spectral density function. The linear elastic and linear viscous – elastic behaviour of soils approach enables to measure soils damping parameters by mentioned box test means, too.